answersLogoWhite

0


Best Answer

The given expression can be simplified to: 3X squared +27

User Avatar

Wiki User

โˆ™ 2018-03-20 13:16:58
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards

Multiplication chart! :)

12 cards

2x1

2x2

2x3

2x4

โžก๏ธ
See all cards

Math and Arithmetic

20 cards

The length of a rectangular floor is 2 feet more than its width The area of the floor is 168 square feet Kim wants to use a rug in the middle of the room and leave a 2 foot border of the floor visib

The perimeter of a rectangle is 18 feet and the area of the rectangle is 20 square feet what is the width of the rectangle

The sum of two numbers is 19 and their product is 78 What is the larger number

A rectangular garden has a perimeter of 48 cm and an area of 140 sq cm What is the width of this garden

โžก๏ธ
See all cards

Add your answer:

Earn +20 pts
Q: How do you do 3X squared plus 18 plus 9?
Write your answer...
Submit
Related questions

What is the answer to 5x squared plus 3x squared plus 9?

The given expression can be simplified to: 8x squared +9


Factor 9x squared minus 6xy plus y squared minus 81?

9x2 - 6xy + y2 - 81 = (3x - y)2 - 81 = (3x - y - 9)*(3x - y + 9)


What is the value of the discriminant of x squared plus 3x plus 9?

-27


How do you factor 9x squared plus 27x plus 18?

Divide the entire equation by 9. (9x2 + 27x + 18)/9 would then be 9(x2 + 3x +2) The factors of this equation would be 9(x + 1)(x + 2)


What is 9x squared minus 6xy plus y squared minus 81 factored as?

9x2 - 6xy + y2 - 81 = (3x - y)2 - 92 = (3x - y - 9)(3x - y + 9)


Factor 24 cubed plus 27x squared - 8x - 9?

(8x + 9)(3x^2 - 1)


3x plus 9 equals 27?

27-9 =18. 18/3 =6


Simplify the algebraic expression 7x squared minus 4y plus 3x squared plus 5y plus 2 and evaluate it for x equals 3 and y equals 9?

7(3y-2)-(-4y+9)


What must be added to 5 x squred plus 6x plus 9 so that the sum is negative x squered plus 3x plus 3?

5x^2 + 6x + 9 + (?) = -x^2 +3x + 3 (?) = -5x^2 -6x - 9 -x^2 +3x + 3 = -6x^2 -3x -6 Ans: -6x squared +3x -6


What is Factor x squared plus 3x minus 54?

(x - 6)(x + 9)


How do you factor x squared plus 3x - 54?

57


What is the answer to -9x2-3x squared?

I got 441. -9 x 2 = -18. -18 - 3 = 21 21 x 21 = 441


What is 4x plus 6 minus7x plus 9 equals 18?

4x+6-7x+9=18-3x+15=18-3x=3x=-1


What is 27x squared -90x plus 27 factored to?

27x2 - 90x + 27 = 9*(3x - 1)*(x - 3)


What is 6 squared plus 9 squared?

6 squared plus 9 squared is equal to 117.


How do you factor x cubed plus 9x squared plus 2x plus 18?

Since the problem has 4 terms, first you factor x cubed plus 9x squared, then you factor 2x plus 18. So when you factor the first two term, you would get x sqaured (x plus 9). Then when you factor the last two terms and you get 2 (x plus 9). Ypure final answer would be (x squared plus 2)(x plus 9)


X squared plus 3x-54?

-51


1 divided by 3x plus 6 equals 9?

1/3x + 6 = 9 Restating the problem x + 18 = 27 I multiplied by 3 x = 9 I subtracted 18 from 27


3x squared -5x plus 1 plus 8x squared - 2x -9?

(5x 2 - 8x + 1) + (2x 2 - 4x - 11)


What is the answer to 3x plus 9?

3x plus 9 equals what?


Y equals 5x plus 18 y equals 2x plus 9?

5x+18 = 2x+9 5x-2x = 9-18 3x = -9 x = -3 and y = 3


How do you factor 48x squared plus 139x plus 63?

48x2+139+63 = (3x+7)(16x+9) when factored and worked out with the help of the quadratic equation formula


What is the complete factor of this problem 4x3 plus 12x2 plus 3x plus 9?

4x3+12x2+3x+9


Generating equivalent expression 3x-9 plus 3x plus 5?

The equivalent expression of 3x-9 plus 3x plus 5 is negative 4.


Two x take away one over 9 plus x take away one over six equals three x plus five over twelve?

2x-1/9+x-1/6=3x+5/122x+x=3x 1/9-1/6=-1/183x-1/18=3x+5/12-3x........-3x-1/18=5/12+1/18 +1/18No Answer: 0≠17/36